Jejunal Atresia with Santulli Procedure on Neonate 10 Days: Case Report - Nisa Alyananda Ritonga; Nurmasithah Nurmasithah; Hermanto Hermanto (Riviera Publishing, 2025)
Jejunal atresia is a rare congenital anomaly causing intestinal obstruction in neonates, necessitating prompt diagnosis and surgical intervention for optimal outcomes. This case report highlights the management of a 10-day-old neonate presenting with persistent bilious vomiting, abdominal distension, and failure to pass meconium. Diagnostic imaging confirmed jejunal atresia, and the Santulli procedure was performed to restore intestinal continuity while allowing distal bowel decompression. Despite postoperative challenges, including sepsis and unstable vital signs, the case underscores the importance of timely surgical intervention and comprehensive postoperative care. The study aims to identify risk factors, diagnostic approaches, and effective management strategies for jejunal atresia in neonates. Research methods included clinical evaluation, imaging (X-ray), and exploratory laparotomy, followed by the Santulli procedure. Findings revealed type IV atresia with multiple lesions, treated surgically. However, the patient succumbed to sepsis 26 hours post-operation, emphasizing the critical need for early intervention and robust postoperative monitoring. The implications of this research stress the urgency of early diagnosis, appropriate surgical techniques, and multidisciplinary care to improve survival rates in such cases.